The Principal's Management in Developing Teachers' Pedagogical Competence for Quality Improvement at PAUD Terpadu KB dan TK Melati Putih Plus Samarinda - Ninthia, Devita Sindy; Dwiyono, Yudo; Akhmad; Mulawarman, Widyatmike Gede; Nurlaili, Nurlaili; Yahya, Masrur (EduLine: Journal of Education and Learning Innovation, 2025)
Early childhood education (PAUD) plays an important role in children's basic development, but the quality of education provided in integrated PAUD KB and TK Melati Putih Plus still faces significant problems, especially related to teacher pedagogical competence. Many teachers in PAUD still have not fully mastered the skills in designing effective, interactive learning that is in accordance with the needs of early childhood. This study aims to describe the planning, organization, implementation, and supervision in developing teacher pedagogical competence in integrated PAUD KB and TK Melati Putih Plus Samarinda. The research method used is a case study with a qualitative approach. The sources of research data are the principal, vice principal, teachers, supervisors, and parents. Data collection was conducted through in-depth interviews, observation, and documentation. The results of the study indicate that effective planning involves creating a safe and comfortable learning environment, implementing student-centered learning, and ongoing assessment. Good organization includes clear division of tasks, collaboration between teachers, and parental involvement. Learning implementation is carried out through direct monitoring, periodic evaluation, and the use of technology to support interactive learning. Supervision is carried out through evaluation of the Daily Learning Implementation Plan (RPPH), direct observation, and constructive feedback. All of these effective principal management practices contribute to improving teacher pedagogical competence and overall education quality.